Autoimmune hepatitis and pregnancy. (October 2020) - Braga, A.; Vasconcelos, C.; Braga, J.
Abstract: Autoimmune hepatitis (AIH) is a rare liver disease of autoimmune aetiology that classically affects women at reproductive age. Diagnosis of AIH is not always straightforward, and other causes of chronic liver disease must be excluded. Pregnancy in patients with AIH is associated with an increased risk of adverse maternal and foetal outcomes. In older studies, the incidence of adverse outcomes was high, with a large number of flare-ups, maternal deaths, and perinatal complications. In the most recent series, improved care based on multidisciplinary surveillance, a larger number of patients treated before and during pregnancy, and reduced incidence of cirrhosis at conception have led to better maternal outcomes and a live-birth rate similar to that in the general population. Nonetheless, AIH is still associated with preterm birth, foetal growth restriction, and unpredictable liver flares, and it represents a group of patients who need close evaluation during pregnancy. Highlights: AIH live birth rate is similar to that in the general population. AIH is associated with adverse outcomes during pregnancy. Surveillance of these patients must be performed by expert multidisciplinary teams. Azathioprine seems to be safe for use during pregnancy.